Application of virtual planning for improvement of four-wall orbitotomy in surgical treatment of craniofacial pathologies - Рагимов, Чингиз Рагим оглы; Фарзалиев, Исмаил Махмуд оглы; Гаджиева, Гюнель Ильхам кызы (Actual Dentistry, 2019)
Purpose. Improvement of efficiency of surgical treatment of patients with craniofacial deformities by application of virtual modelling in preoperative planning of fourwall orbitotomy. Materials and methods. Current study was done on patients with Cruzon syndrome, and frontonasal dysplasia. Patients passed through accurate clinical investigation done by maxillofacial surgeon, ophthalmologist, neurologist, neurosurgeon, and ENT specialist. Acquired data was documented and augmented by photo and video data received by usage of professional camera Nikon D800 (Minato, Tokyo, Japan). Computer tomography was done on TOSHIBA CT scanner (Aquilion PRIME, Minato,Tokyo, Japan). Acquired data was imported into Materialise Mimic 21 Research virtual planning software package (Leuven, Belgium), followe d by appropriate virtual measurements, that were used during surgical procedure. Surgery was executed under general anesthesia in collaboration of maxillofacial surgeon, neurosurgeon and ENT surgeon. Monobloc creation, which part was our-wall orbitotomy was done via coronary approach. In postoperative period careful clinical and radiological comparison was done. Results. In both clinical cases based no postoperative CT scan data a compliance of real transpositioning of osseous fragments to preplanned was noted. In case of Cruzon syndrome real transpositioning was 11.89 mm; in case of frontonasal dysplasia due to medialization of the orbits intercanthal distance decreased form 34.02 to 24.02 mm, and width of Glabella from 44.09 to 29.84 mm respectively, that was corresponding to preplanned transpositioning. Moreover, because of combination of surgical (osteotomy in creation of monobloc) and orthodontic treatment qualitive changes were noted within occlusion as well. Thus, in first clinical case application of distraction method of traspositioning in combination of orthodontic treatment lead to exchanging of 3rd class occlusion to 2nd; in second case 2nd class and cross-bite occlusion exchanged to 1st class, that finally lead to restoration of upper airways, meal and speech functions. Conclusions. Application of virtual preoperative planning significantly increasing the outcomes of four-wall orbitotomy in treatment of different craniofacial deformities. Combination of surgical and orthodontic approaches allows to solve issues relate to functional and esthetic parameters of both orbits and occlusion. Key words: four-wall orbitotomy, craniofacial deformities, virtual planning.